2011
DOI: 10.1007/s00264-011-1419-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of idiopathic scoliosis and sequence alignment analysis of multiple candidate genes

Abstract: Purpose To investigate the effects of genetic factors on idiopathic scoliosis (IS) and genetic modes through genetic epidemiological survey on IS in Chongqing City, China, and to determine whether SH3GL1, GADD45B, and FGF22 in the chromosome 19p13.3 are the pathogenic genes of IS through genetic sequence analysis. Methods 214 nuclear families were investigated to analyse the age incidence, familial aggregation, and heritability. SH3GL1, GADD45B, and FGF22 were chosen as candidate genes for mutation screening i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
8
0
7
Order By: Relevance
“…They also show a high degree of genetic heterogeneity in autosomal dominant or multifactorial inheritance patterns with major genes. Many studies identified idiopathic scoliosis-susceptible genes (such as SH3GL1, GADD45B, and FGF22) and linked them to idiopathic scoliosis, but these genes are not to all idiopathic scoliosis cases (35)(36)(37)(38). There is no doubt that idiopathic scoliosis is a hereditary disease, so finding its related pathogenic genes is of great significance for the prevention or treatment of idiopathic scoliosis, and it must be a hot spot for future research.…”
Section: Discussionmentioning
confidence: 99%
“…They also show a high degree of genetic heterogeneity in autosomal dominant or multifactorial inheritance patterns with major genes. Many studies identified idiopathic scoliosis-susceptible genes (such as SH3GL1, GADD45B, and FGF22) and linked them to idiopathic scoliosis, but these genes are not to all idiopathic scoliosis cases (35)(36)(37)(38). There is no doubt that idiopathic scoliosis is a hereditary disease, so finding its related pathogenic genes is of great significance for the prevention or treatment of idiopathic scoliosis, and it must be a hot spot for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of idiopathic scoliosis has been reported in a few studies with different methodologies supporting the importance of hereditary factors ( 5 , 7 , 22 ). However, the proportion of the observed variance in idiopathic scoliosis that is attributed to genetics is highly uncertain.…”
Section: Introductionmentioning
confidence: 88%
“…Characteristics of the protein that is encoded by C17orf67 are not studied well [196]. Other genes SNPs that have been reported as having association with AIS are SH3GL1 [197], LAPTM4B [119], IFG1 [119], MMP9 [198], HTR1A [199], and TIMP2 [200]. Axial Biotech Inc. [202] has developed a test to identify patients with low risk of scoliotic curve progression using 53 genetic markers.…”
Section: Genetic Factors Study Of Ais In Twins Demonstratedmentioning
confidence: 99%